2017
DOI: 10.1038/s41598-017-07308-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against Modified NS1 Wing Domain Peptide Protect Against Dengue Virus Infection

Abstract: Dengue is the most common mosquito-transmitted viral infection for which an improved vaccine is still needed. Although nonstructural protein-1 (NS1) immunization can protect mice against dengue infection, molecular mimicry between NS1 and host proteins makes NS1-based vaccines challenging to develop. Based on the epitope recognized by the anti-NS1 monoclonal Ab (mAb) 33D2 which recognizes a conserved NS1 wing domain (NS1-WD) region but not host proteins, we synthesized a modified NS1-WD peptide to immunize mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 54 publications
4
80
0
Order By: Relevance
“…Lack of protective NS1 immunity is independent of mouse background Previous studies that reported NS1-mediated protection were conducted in mouse strains such as IFNAR −/− ; Beatty et al, 2015) and STAT1 −/− (Wan et al, 2017;Lai et al, 2017), both on the C57BL/6 background. We thus questioned whether the discrepancy between our observations and the earlier studies could be explained by a difference in mouse background.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of protective NS1 immunity is independent of mouse background Previous studies that reported NS1-mediated protection were conducted in mouse strains such as IFNAR −/− ; Beatty et al, 2015) and STAT1 −/− (Wan et al, 2017;Lai et al, 2017), both on the C57BL/6 background. We thus questioned whether the discrepancy between our observations and the earlier studies could be explained by a difference in mouse background.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, NS1 may represent an important viral factor that causes vascular leakage and glycocalyx degradation during DENV infection. Indeed, antibodies against NS1 have been shown to be protective against DENV infection in mice [ 17 , 51 , 52 ]. Furthermore, MIF may represent the primary host factor that mediates NS1-induced glycocalyx degradation.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the monocyte infiltration in brain tissues, the slices of brain tissues were first received immunohistochemistry (IHC) staining with anti-Ly6C antibody (Abcam), and then the degree of monocytes infiltration was digitally quantified by ImageJ software [ 45 47 ]. In brief, the staining patterns of Ly6C were detected by EVOS FL Cell Imaging System (Thermo Fisher Scientific), and the blot signals from the digital images were further analyzed by Image J software (NIH, USA).…”
Section: Methodsmentioning
confidence: 99%